The answer is:103
7 goes into 7 once, then you subtract 7 from 7 which is zero. Bring down the 2 and it goes in 0 times, so you put zero on top and subtract, bring down the 1 then you get 21, which goes in 3 times.
Hope it helps!!
You know where the glacier is now, and how far it moves in
one year. The question is asking how close to the sea it will be
after many years.
Step-1 ... you have to find out how many years
Step-2 ... you have to figure out how far it moves in that many years
Step-3 ... you have to figure out where it is after it moves that far
The first time I worked this problem, I left out the most important
step ... READ the problem carefully and make SURE you know
the real question. The first time I worked the problem, I thought
I was done after Step-2.
============================
Step-1: How many years is it from 2010 to 2030 ?
(2030 - 2010) = 20 years .
Step-2: How far will the glacier move in 20 years ?
It moves 0.004 mile in 1 year.
In 20 years, it moves 0.004 mile 20 times
0.004 x 20 = 0.08 mile
Step-3: How far will it be from the sea after all those years ?
In 2010, when we started watching it, it was 6.9 miles
from the sea.
The glacier moves toward the sea.
In 20 years, it will be 0.08 mile closer to the sea.
How close will it be ?
6.9 miles - 0.08 mile = 6.82 miles (if it doesn't melt)
Answer:
7.2111(4 decimal places)
Step-by-step explanation:
a squared by b squared=c squared
36 + 16 is 52, so then you need to square root 52 which is 7.2111 to 4 decimal places. I hope you benefit from this. Cheers
Answer
B., C.
Step-by-step explanation:
Since the 'E' in the middle
it represents that the angle forms at the vertex E
Answer:
-6
Step-by-step explanation:
![\frac{(t-r)}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B%28t-r%29%7D%7B3%7D)
input the numbers
![\frac{(-6-12)}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B%28-6-12%29%7D%7B3%7D)
do the problem in the parentheses first
-6-12 = -18
now it becomes
![-\frac{18}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B18%7D%7B3%7D)
simplify and you'll get
-6
this is because -18 ÷ 3 =
-6